Urine Cytology in Patients with Long Standing Dialysis - Kattab, Yarub I; Al-Qazzaz, Mutaz A.; Mousa, Liqaa R (AL-Kindy College Medical Journal, 2007)
Background: Dialysis is in common use to treat patientswith end stage renal failure .However longstanding dialysisharboring some cellular changes in various body fluids.This study was conducted in order to detect these changesin urine.Objective: The study was conducted to detect cellularchanges in urine of patients with longstanding dialysis.Method: Fifty-three urine samples were examinedcytologically obtained from patients with longstandingdialysis during 6 months period. Freshly voided midstreamurine samples were taken . Samples were centrifuged and 2to 3 drops of sediments were smeared on 2 glass slides andfixed in 95% ethyl alcohol then stained with Hand E stainto be evaluated.Results: Gross physical examination of all urine sampleswere neither purulent nor hemorrhagic .Microscopicallythere was increased exfoliation of urothelial cells except in9 cases. No significant cytological atypia were seen in allurine samples. Excessive exfoliation in the absence ofsignificant inflammation, hemorrhage and cytologicalatypia compared with control group.Conclusion: The study revealed that some cytologicalchanges do occur in the urothelial cells of patients withlongstanding dialysis. These changes need further attentionand study to disclose their causes.